The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/ja029550i
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Thin-Film Solid-State Electroluminescent Devices Based on Tris(2,2‘-bipyridine)ruthenium(II) Complexes

Abstract: The factors affecting the operating life of the light-emitting electrochemical cells (LECs) based on films of tris(2,2'-bipyridine)ruthenium(II) both in sandwich (using an ITO anode and a Ga:Sn cathode) and planar (using interdigitated electrode arrays (IDAs)) configurations were investigated. Stability of these devices is greatly improved when they are produced and operated under drybox conditions. The proposed mechanism of the LEC degradation involves formation of a quencher in a small fraction of tris(2,2'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
217
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(231 citation statements)
references
References 43 publications
(88 reference statements)
11
217
0
3
Order By: Relevance
“…47,48 The utilization of IS in case of iTMC-LECs, especially with respect to the evaluation of physical processes, is, however, rather scarce. It was applied to study degradation in these devices 49,50 to make statements about the impact of ion mobilities, 51 to prove electrochemical junction formation and to highlight influencing variables on the junction width, and to estimate the transient thickness of the p-i-n junction during operation. 38,52 One of the latest publications in the field of LECs used IS to demonstrate that pLECs and iTMCLECs are essentially behaving as one class of device.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 The utilization of IS in case of iTMC-LECs, especially with respect to the evaluation of physical processes, is, however, rather scarce. It was applied to study degradation in these devices 49,50 to make statements about the impact of ion mobilities, 51 to prove electrochemical junction formation and to highlight influencing variables on the junction width, and to estimate the transient thickness of the p-i-n junction during operation. 38,52 One of the latest publications in the field of LECs used IS to demonstrate that pLECs and iTMCLECs are essentially behaving as one class of device.…”
Section: Introductionmentioning
confidence: 99%
“…[14] The origin of the low lifetimes of iTMC-based electroluminescent devices has been studied in detail only for devices using [Ru(bpy) 3 ] 2þ (bpy ¼ 2,2 0 -bipyridine) as the active component. [15,16] The intrinsic instability of the iTMC under working conditions was identified as the primary and predominant reason for device degradation. Moreover, these studies revealed that the instability of the iTMC complex leads with participation of water molecules to the generation of degradation products that act as efficient luminescence quenchers.…”
mentioning
confidence: 99%
“…The disadvantage of LECs is the short operating lifetime, in the order of hours to days, compared to OLEDs. [3][4][5] We have recently reported the use of intra-and intermolecular face-to-face p-stacking for the stabilisation of the ground and excited state of electroluminescent iridium complexes and shown that this leads to exceptionally long-living LEC devices. 6,7 The long lifetimes of these devices establish LECs as a viable alternative to OLED technology.…”
mentioning
confidence: 99%